Umma Application: Digital Da'wah and the Young Generation in the Era of Disruption - Hopizal Hopizal; Fahrurrazi Fahrurrazi (Kawanua International Journal of Multicultural Studies, 2020)
Da'wah is not only done through social media such as Facebook, Instagram, Twitter, and YouTube. However, preaching is done through free applications that are familiar today. This article tries to specifically examine the Umma Application as a medium for da'wah for young people who are developing significantly. The purpose of this article is to understand and dig deeper into the dakwah process carried out by young figures by uploading da'wah content from religious figures such as Ustad Abdul Somad, Ust Adi Hidayat, Aa Gym, and other figures in the umma application. The method used by researchers in this article is a descriptive qualitative method with the Teun A Van Dijk model of discourse analysis technique, to analyze the religious content it conveys. The results of this study indicate that digital da'wah has a great influence on people's attitudes, perspectives, and behavior with an audio-visual da'wah model. Umma is a da'wah application that has a large enough user among young people creating a new virtual space to access knowledge. Da'wah through the umma application certainly has a major influence on the behavior, attitudes, and points of view of young people when watching videos and reading the uploaded images as a process of proselytizing in the umma application.